Falsification Test of The National Resilience Concept as Indonesian Geostrategic Doctrine - Juniawan Priyono; Herman Herman; Purnomo Yusgiantoro (The Republic of Indonesia Defense University, 2017)
This study aims to prove the truth of national resilence concept by using deductive phenomenological interpretive qualitative methods with epistemology of geostrategy as a main objective. Popper’s falsification test is intended to gather evidence on which the geostrategic peripheral is applied to the national resilience concept, rather than reject the conception. The required data includes the national resilience concept and an epistemology of geostrategy to explain geostrategic realities in a sistematic hierarchy, using historical documents, scientific publications and also interviews. This study has shown that the national resilience concept sits outside the geostrategic periphery, despite some evidence of geostrategic validity. The evidence indicating the applicability of geostrategy includes (1) Formulation of national objectives and; (2) Consideration of geography and geopolitical conditions